Multiplicity of human scent signature - Petr Doležal; Kenneth G. Furton; Jana Lněničková; Pavlína Kyjaková; Veronika Škeříková; Irena Valterová; Ludvík Pinc; Štěpán Urban (Egyptian Journal of Forensic Sciences, 2019)
Abstract Background In this paper, the term “human scent signature” refers to a group of chemical compounds in a human scent trace that are in certain relative concentrations that make an unambiguous identification of persons possible. At the present time, the scent identification of persons is performed using specially trained canines. However, the scent identification mechanism as well as the molecular composition of the human scent signature is entirely unrecognized. Delimitations of the group of chemical compounds according to their volatilities that specially trained canines use for the scent identification of persons were initially the main aim of this study. Methods Eleven volunteer scent samples were split into three groups of chemical compounds, i.e., into three disjointed scent fractions with different volatilities of the compounds via preparative gas chromatography. The human scent signatures were searched in these separated scent fractions using six specially trained canines (female German Shepherds). Results The canines were able to identify individual persons successfully using different scent fractions. From this fact, it follows that one scent trace can contain more than only one group of scent compounds that can be used for scent identification by the trained canines. This observed phenomenon was named as “the multiplicity of the human scent signature” in this study. The scent identification line-up procedure provided the following results: The poorly volatile fraction resulted in an 85% success rate in the scent identification procedure. The middle fraction resulted in a 58% success rate, and the highly volatile fraction resulted in a 30% success rate. Conclusions In this study, it was found that the human scent sample contains more than one group of scent compounds; according to which the trained canines are able to identify human individuals. It means that the human scent sample contains more than only one scent signature. The authors of this research believe that results of this study will open a broad discussion about the multiplicity of the human scent signature, primary scent molecules, optimal canine training, and in general, the scent identification method in many countries.